The doll in the garden : a ghost story - Hahn, Mary Downing (Clarion Books, 2007)
After Ashley and Kristi find an antique doll buried in old Miss Cooper's garden, they discover that they can enter a ghostly turn-of-the-century world by going through a hole in the hedge.